Kebebasan Berpendapat dalam Islam : Antara Hak Warga Negara dan Batasan Syariah - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Naila Luthfiyana; Faren Darnuansyah; Septina Sari Handayani (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
One of the human rights protected by several national and international legal instruments is freedom of opinion. In a democratic country like Indonesia, it is protected under Article 28e Paragraph (2) and (3) of the 1945 Constitution and Article 19 of the Universal Declaration of Human Rights. However, in Islam, freedom of opinion is not absolute, meaning that it has a basis based on Sharia principles to uphold the common good. This study uses a qualitative literary analysis method in conjunction with a descriptive-analytical approach with relevant aspects of Islamic law and national regulations. According to the results of the study, Islam encourages behavior that is consistent with the law and does not conflict with Sharia principles, such as not requiring slander, hoaxes, or division. As stated in positive legal regulations, the state also has an obligation to maintain harmony between individual rights and public welfare. Therefore, it is necessary to align Sharia law and the right to freedom of opinion to create a democratic society that still respects religious norms.